The Effect of Family Caregiver Empowerment Model Intervention on Fear of Hypoglycemia in People with Type-2 Diabetes Mellitus - Rondhianto Rondhianto; Kushariyadi Kushariyadi; M. Nauval Rahmatullah (Nurse Media: Journal of Nursing, 2024)
Background: The family plays a vital role in T2DM self-management, but many families need to understand their role and function as caregivers. This lack of understanding can increase the burden of disease management, contributing to the emergence of psychological problems in people with T2DM, such as fear of hypoglycemia, which in turn worsens blood glucose control. The Family Caregiver Empowerment Model (FCEM) intervention is one model that can be used to empower families as caregivers in T2DM self-management.